A study on the prevalence of heavy metals, pesticides, and microbial contaminants and antibiotics resistance pathogens in raw salad vegetables sold in Dhaka, Bangladesh. Issue 2 (February 2019) - Ahmed, Sunzid; Siddique, Md. Abubakkar; Rahman, Matiur; Bari, Md. Latiful; Ferdousi, Shahnila
Abstract: The presence of undesirable heavy metals, pesticide residues, and microbial contaminants in fresh produces is a worldwide public health concern. This study was undertaken to evaluate the residual pesticides (Diazinon, Malathion, Cypermethrin, Dimethoate, Quinalphos, and Chloropyrofos), heavy metal contamination (Pb, Cd, and Cr), and microbiological quality and safety of 4 common raw salad vegetables (RSVs) samples from different local markets in Dhaka. Results showed the presence of heavy metals residues were within the acceptable limits of local and international standards. None of the above-mentioned pesticides were found in tomato and cucumber samples but presence of Dimethoate was noticed in 13 coriander samples (12.94–158.3 μg/kg) and 7 lettuce samples (9.6–74.8 μg/kg) exceeding the maximum permissible limit of EU guideline. The microbiological analysis showed irrespective of RSV types, total aerobic bacteria was present in higher number (4.0–7.0 log CFU/g), whereas 3.36–5.57 log CFU/g coliform count was recorded. In comparison with retail markets, lower level of total aerobic, and coliform bacterial presence was observed in the samples collected from sophisticated shops, but presence of E. coli and Salmonella spp. were evident in more than 60% samples in these shops. However, 50% and 33% samples from wholesale and retail markets respectively were noticed to be contaminated with Staphylococcus spp. Irrespective of RSV types, isolated E. coli were found resistance to 2–5 different antibiotics, where Salmonella spp. isolated from cucumber and coriander leaves showed resistance against 4–8 different antimicrobials. Therefore, the study results demonstrated that, the presence of residual pesticides, multidrug resistant E. coli and S almonella spp. in the RSV samples posing concern when consumed raw. The regulatory bodies are expected to monitor and ensure the overall quality standards are in place and practiced by food producers and marketers responsible for handling and distribution of RSVs.